2014
DOI: 10.1088/0957-4484/25/15/155303
|View full text |Cite
|
Sign up to set email alerts
|

Anti-counterfeit nanoscale fingerprints based on randomly distributed nanowires

Abstract: Counterfeiting is conducted in almost every industry, and the losses caused by it are growing as today's world trade continues to increase. In an attempt to provide an efficient method to fight such counterfeiting, we herein demonstrate anti-counterfeit nanoscale fingerprints generated by randomly distributed nanowires. Specifically, we prepare silver nanowires coated with fluorescent dyes and cast them onto the surface of transparent PET film. The resulting non-repeatable patterns characterized by the random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
79
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 20 publications
0
79
0
1
Order By: Relevance
“…With the availability of a plethora of nanobarcodes, they have been employed for many applications such as detection of biomolecules (nucleic acid and proteins), imaging, security, drug delivery, theranostics, etc. 7,11,[14][15][16][17][18][19][20][21] Decoding of signals from these nano-barcodes depends on their encoding technique. For instance, nano-barcodes with fluorescent encoding elements requires fluorescence microscopy or spectra measurement for detection, whereas nano-barcodes of different light reflectivity pattern can be read out by reflectance optical microscopy.…”
Section: Thoriq Salafimentioning
confidence: 99%
“…With the availability of a plethora of nanobarcodes, they have been employed for many applications such as detection of biomolecules (nucleic acid and proteins), imaging, security, drug delivery, theranostics, etc. 7,11,[14][15][16][17][18][19][20][21] Decoding of signals from these nano-barcodes depends on their encoding technique. For instance, nano-barcodes with fluorescent encoding elements requires fluorescence microscopy or spectra measurement for detection, whereas nano-barcodes of different light reflectivity pattern can be read out by reflectance optical microscopy.…”
Section: Thoriq Salafimentioning
confidence: 99%
“…However, they are still clonable because the encoding mechanisms are predictable and deterministic. Although physical unclonable function (PUF)‐based encoding can provide unreplicable codes, previous demonstrations lacked sufficient intelligent code control mechanisms as well as practical applicability for a wide range of products. Here, we present an unclonable and universally adaptable anti‐counterfeiting strategy that mimics the nature of human fingerprints by encrypting polymeric particles with randomly generated silica film wrinkles.…”
mentioning
confidence: 99%
“…Therefore, for strong authentication, it is essential to adopt nondeterministic encoding to guarantee unique and intrinsically irreproducible code outputs. PUF‐based encodings gained substantial recognition but they suffer from practical constraints such as orientation‐sensitive optical codes, short lifespan of fluorescent material, and narrow‐ranged product applicability . Above all, most of these nondeterministic encoding architectures focused on expanding code randomness at the expense of configurable features that are of industrial necessity such as tunable code complexity and versatility in decoding strategy.…”
mentioning
confidence: 99%
“…The first relies on the point-by-point comparison of digitized patterns 8 . Kim et al 20 reported an anticounterfeiting tag featuring randomly distributed nanowires coated with fluorescent dyes, and recorded the location and the color of nanowires to realize identification. The second depends on pattern recognition 8 .…”
mentioning
confidence: 99%
“…Chemical methods have been extensively adopted to produce anticounterfeiting tags, such as luminescent nanomaterial-based security inks 22 , spectrally distinct upconversion nanocrystalbased particle barcodes 23 , nucleic acid 24,25 or peptide 26 based molecular tags, and so on. Such chemically fabricated PUF labels have many advantages 17,20,21,[27][28][29] . Firstly, chemical approaches are stochastic processes, as required for PUFs.…”
mentioning
confidence: 99%